Evaluation of Antimalarial Activity of Hydromethanolic Crude Extract and Solvent Fractions of the Leaves of Nuxia congesta R. Br. Ex Fresen (Buddlejaceae) in Plasmodium berghei Infected Mice - Fenta M; Kahaliw W (Dove Medical Press, 2019)
Melshew Fenta,1 Wubayehu Kahaliw2 1University of Gondar Specialized Referral Teaching Hospital, University of Gondar, Gondar, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Wubayehu KahaliwDepartment of Pharmacology, College of Medicine and Health Sciences, University of Gondar, P.O, Box 196, Gondar, EthiopiaTel +251 910532412Email kahaliw_w@yahoo.comBackground: In Ethiopia, malaria control has been complicated due to resistance of the parasite and its vectors to the current drugs. Therefore, new drugs are required to avert the problem posed by drug-resistant Plasmodium strains. There is need to investigate alternative sources of antimalarial agents and plants are potential source of antimalarial drugs. This study aimed to investigate the antimalarial activity of the leaves of N. congesta crude extract (hydromethanolic extract) and solvent fractions (n-hexane, chloroform, and aqueous fractions of crude extract) traditionally used to treat malaria in many parts of Ethiopia.Methods: Acute oral toxicity of the leaves of N. congesta extract was assessed in mice up to a dose of 5,000 mg/kg body weight. Antiplasmodial activities of crude extract and solvent fractions were assessed in P. berghei infected female Swiss albino mice models using the Peter’s 4-day suppressive test. The curative activities of crude extract and fractions were evaluated using Rane’s test.Results: Plant extract exhibited no signs of toxicity on mice at a dose of 5,000 mg/kg body weight. Crude extract showed significant parasitemia suppressions at doses of 500 mg/kg (P<0.05), 750 mg/kg (P<0.01), and 1,000 mg/kg (P<0.001) as compared to negative control in the Peter’s 4-day suppressive test, but failed to reach a significant level at 500 mg/kg and 750 mg/kg in the curative test (Rane’s test). Aqueous fraction showed significant parasitemia suppression at a dose of 400 mg/kg (P<0.05) in curative test and 600 mg/kg (P<0.05) in Peter’s 4-day suppressive and curative tests. Maximum suppressive effects of extract (58.13%) and aqueous fraction (44.9%) were observed at the highest doses administered.Conclusion: Hydromethanolic leaf extract of N. congesta and its aqueous fraction exhibited antimalarial activities. The antimalarial activity and lack of acute toxicity are suggested to uphold the earlier claims made by the Ethiopian traditional practitioners.Keywords: parasitemia, antimalaria, extract, suppression, curative